Autophagy inhibitor 3-methyladenine alleviates overload-exercise-induced cardiac injury in rats - LIU Hua; LEI Hui; SHI Yue; WANG Jin-ju; CHEN Ning; LI Zhang-hua; CHEN Yan-fang; YE Qi-fa; YANG Yi (Acta Pharmacologica Sinica, 2017)
Overload-exercise (OE) causes myocardial injury through inducing autophagy and apoptosis. In this study we examined whether an autophagy inhibitor 3-methyladenine (3-MA) could alleviate OE-induced cardiac injury. Rats were injected with 3-MA (15 mg/kg, iv) or saline before subjected to various intensities of OE, including no swim (control), 2 h swim (mild-intensity exercise, MIE), 2 h swim with 2.5% body weight overload (moderate OE; MOE), 5% overload (intensive OE; IOE) or 2.5% overload until exhausted (exhaustive OE; EOE). After OE, the hearts were harvested for morphological and biochemiacal analysis. The cardiac morphology, autophagosomes and apoptosis were examined with H&E staining, transmission electron microscopy and TUNEL analysis, respectively. Autophagyrelated proteins to (LC3-II/I and Beclin-1) and apoptosis-related proteins (Bcl-2/Bax) were assessed using Western blotting. Our results showed that compared with the control, MIE did not change the morphological structures of the heart tissues that exhibited intact myocardial fibers and neatly arranged cardiomyocytes. However, IOE resulted in irregular arrangement of cardiomyocytes and significantly increased width of cardiomyocytes, whereas EOE caused more swollen and even disrupted cardiomyocytes. In parallel with the increased OE intensity (MOE, IOE, EOE), cardiomyocyte autophagy and apoptosis became more and more prominent, evidenced by the increasing number of autophagosomes and expression levels of LC3-II/I and Beclin-1 as well as the increasing apoptotic cells and decreasing Bcl-2/Bax ratio. 3-MA administration significantly attenuated OE-induced morphological changes of cardiomyocytes as well as all the autophagy- and apoptosis-related abnormalities in MOE, IOE and EOE rats. Thus, the autophagy inhibitor 3-MA could alleviate OE-induced heart injury in rats.